Table of Content - -, (Journal of medical and pharmaceutical sciences, 2025)
Table of Content:1. The extent of Yemeni society's acceptance of the application of artificial intelligence in the field of dentistry A case study in the city of TaizDr. Ahmed Mohammed Mahmood Abdulhameed ,Eng. Amer Abdo Mohammed Sufyan2. The Effect of Thermal Treatment on the Concentration of Common Antibiotics in Cow Milk Samples in SudanDr. Tafaul Awad Mohamed Alawad, Dr. Amira A.A. Behairy,  Dr. Muhanad M. A. Elhag,  Dr. Shakir Saleem
Keywords: Journal of Medical and Pharmaceutical Sciences